Thyroid hormone shapes craniofacial bones during postembryonic zebrafish development. Issue 1 (25th March 2022) - Keer, Stephanie; Storch, Joshua D.; Nguyen, Stacy; Prado, Mia; Singh, Rajendra; Hernandez, Luz Patricia; McMenamin, Sarah K.
Abstract: Changing the shape of craniofacial bones can profoundly alter ecological function, and understanding how developmental conditions sculpt skeletal phenotypes can provide insight into evolutionary adaptations. Thyroid hormone (TH) stimulates metamorphosis and regulates skeletal morphogenesis across vertebrates. To assess the roles of this hormone in sculpting the craniofacial skeleton of a non‐metamorphic vertebrate, we tested zebrafish for developmental periods of TH‐induced craniofacial shape change. We analyzed shapes of specific bones that function in prey detection, capture and processing. We quantified these elements from late‐larval through adult stages under three developmental TH profiles. Under wild‐type conditions, each bone progressively grows allometrically into a mature morphology over the course of postembryonic development. In three of the four bones, TH was required to sculpt an adult shape: hypothyroidism inhibited aspects of shape change, and allowed some components of immature shape to be retained into adulthood. Excess developmental TH stimulated aspects of precocious shape change leading to abnormal morphologies in some bones. Skeletal features with functional importance showed high sensitivities to TH, including the transformator process of the tripus, the mandibular symphysis of the lower jaw, the scutiform lamina of the hyomandibula, and the anterior arm of the pharyngeal jaw. In all, we found that TH is necessary for shaping mature morphology of several essential skeletal elements; this requirement is particularly pronounced during larval development. Altered TH titer leads to abnormal morphologies with likely functional consequences, highlighting the potential of TH and downstream pathways as targets for evolutionary change. Abstract : The tripus is an essential element of the zebrafish Weberian apparatus, which allows the fish to hear. Under wild‐type, euthyroid conditions, the adult tripus adopts a characteristic shape (bottom center). We found that development of the adult shape in this and other craniofacial bones was sensitive to developmental thyroid hormone, and with little thyroid hormone (hypothyroid, bottom left) or excess thyroid hormone (hyperthyroid, bottom right), the elements grow into differing shapes during adulthood, with likely functional consequences Research Highlights: Thyroid hormone shapes the tripus, lower jaw, hyomandibula, and pharyngeal jaw during zebrafish development. Changing developmental thyroid hormone titer modulates the development and ultimate shapes of these craniofacial elements, with evolutionarily‐relevant functional consequences.